Detection of plasmids in Salmonella from poultry and investigating the potential horizontal transfer of antimicrobial resistance and virulence genes - Haijiao Lin; Moussa S. Diarra; Guangqiang Jia; Xin Zhao (Poultry Science)
Antimicrobial resistance genes (ARGs) and virulence genes (VGs) have been widely reported in Salmonella which are major foodborne pathogens from poultry. This study assessed the replicon typing and conjugative ability of plasmids from poultry-derived Salmonella as well as ARGs and VGs carried by these plasmids using an in silico approach. Both PlasmidFinder 2.1 and VRprofile2 were employed to detect plasmids in Salmonella sequences downloaded from the National Center for Biotechnology Information (NCBI) Reference Sequences (RefSeq) database, and then oriTfinder was used to determine the conjugative ability of plasmids. The ARGs and VGs on plasmids were identified by both VRprofile2 and oriTfinder. The phenotypes of ARGs were predicted by ResFinder 4.1 and oriTfinder, while the phenotypes of virulence were predicted by oriTfinder and VRprofile2. We identified 183 plasmid sequences from 309 downloaded sequences. Among them, 77 (42.1 %) plasmids were conjugative, 25 (13.7 %) mobilizable, and 81 (44.3 %) non-mobilizable. Fifty-one plasmids (27.9 %) contained multi-replicons. One hundred and five plasmids carried 58 ARGs, belonging to 12 classes. The most prevalent ARG groups in plasmids were the aminoglycoside, β-lactam, sulfonamide, and tetracycline groups. In addition, 49 plasmids carried 36 different VGs belonging to 13 gene classes. The most prevalent VG groups were the adhesin, type III secretion system, and resistance to complement killing groups. The detected high percentage of conjugative plasmids and existence of many multiple replicons suggest possible high rates of plasmid-mediated horizontal gene transfer (HGT) events. Detection of previously unreported plasmid-borne VG (fdeC) from Salmonella in poultry calls for more vigilant monitoring.